PENGEMBANGAN MODEL KONSERVASI KESEJARAHAN DI SEMARANG BERBASIS TEKNOLOGI INFORMASI - Sodiq, Ibnu; Saraswati, Ufi; Prabowo, Ardhi (Badan Pengembang Konservasi UNNES, 2018)
Semarang has various historical relics and cultural heritages stretching from the Hindu-Buddhist period to contemporary times. The cultural heritage has a strategic meaning in shaping the identity of the city and community in Semarang. With the existence of cultural heritage, society is expected to be able to absorb the values and meanings implied in it. The value is the value of care for the environment and the culture around it. However, community knowledge about the cultural heritages in Semarang City is constrained when information about historical relics is not presented systematically, comprehensively, and easily accessible. Therefore, through this research we aim to: (1) analyze the needs of the community related to cultural heritage information in Semarang City; (2) identify and inventory the existing cultural heritage in Semarang City; (3) developing a model of cultural heritage information system in Semarang City; (4) to analyze the effectiveness of cultural heritage information system model in Semarang City.